2020
DOI: 10.1007/s10973-020-10162-7
|View full text |Cite
|
Sign up to set email alerts
|

Modification of blood serum DSC profiles by sauna treatments in cross-country skiers during the exercise cycle

Abstract: The study has evaluated the effect of sauna treatments on the blood serum of professional crosscountry skiers (3 women and 6 men) during two exercise sessions: the first without any treatments and the second after ten sauna treatments. Aqueous solutions of serum samples from the blood of athletes collected in four stages in both exercise sessions: at rest, after exercise, after 1 h and 24 h rest and additionally only at rest after the first sauna treatment, were measured by means of differential scanning calor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Recently, using differential scanning calorimetry (DSC) in analyzing plasma heat capacity changes, Mourtakos et al [ 85 ] indicated that 5 days of exhaustive physical exercise of highly trained individuals enhanced the thermal stability of plasma albumin shifting its denaturational transition to a higher temperature. In our previous study, using DSC to assess potential alterations in the plasma heat capacity and to register characteristic post-exercise changes in the profile of thermal denaturation transition of serum after the sauna treatments [ 86 ], we indicated that the alterations in the plasma proteome denaturational profiles were not persistent. In accordance with Rocker et al [ 65 ], the change in intravascular plasma protein mass (TPP) was estimated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, using differential scanning calorimetry (DSC) in analyzing plasma heat capacity changes, Mourtakos et al [ 85 ] indicated that 5 days of exhaustive physical exercise of highly trained individuals enhanced the thermal stability of plasma albumin shifting its denaturational transition to a higher temperature. In our previous study, using DSC to assess potential alterations in the plasma heat capacity and to register characteristic post-exercise changes in the profile of thermal denaturation transition of serum after the sauna treatments [ 86 ], we indicated that the alterations in the plasma proteome denaturational profiles were not persistent. In accordance with Rocker et al [ 65 ], the change in intravascular plasma protein mass (TPP) was estimated.…”
Section: Discussionmentioning
confidence: 99%
“…Net total protein gained during and after the exercise test in group T2 was found not to be significantly different from that gained in control (T1). We reported that similar quantities of protein were added to the vascular volume in both the control and the MPHA groups after the exercise test; however, changes in the athlete’s blood serum proteome, conditioning the modification of serum DSC profiles in the session held after sauna treatments, were stronger than those in the session not preceded by treatments [ 86 ].…”
Section: Discussionmentioning
confidence: 99%